Environmental advantages of composite fuels based on industrial wastes and different ranks of coal; MATEC Web of Conferences; Vol. 209 : International Conference on Combustion Physics and Chemistry (ComPhysChem’18) - Nyashina G. S. Galina Sergeevna (2018, 2018)
Title screen